Characterization of the profile of drug intoxications by self-medication in Brazil, from 2010 to 2017 (Research, Society and Development, 2020)
Medicines are of paramount importance in the treatment of diseases, however, their indiscriminate use can cause health risks, mainly through the practice of self-medication. This study aimed to analyze the clinical and epidemiological profile of individuals with intoxications resulting from the practice of self-medication in Brazil. This is an ecological, descriptive, quantitative, population-based study, using secondary data, in which an epidemiological survey was carried out of cases of diseases and conditions due to exogenous intoxication reported in Brazil, in the period from 2010 to 2017, obtained in the Notifiable Diseases Information System (SINAN). Assessing aspects related to notification by toxic agent, 1st symptom and evolution, circumstance, region of notification, Federative Unit and toxic agent-drug. The data were tabulated using the Tabnet program, which were then exported and analyzed in the Microsoft Office Excel 2019 program. Based on the results, it was observed that 565,271 cases were reported by toxic agents in the period 2010-2017 in Brazil. Of these, it was found that the drug was the most frequent toxic agent, corresponding to 298,976 (52.8%) of the total cases. The predominant circumstance of the use of the toxic agent-drug occurred was accidental, 42,968 (36.3%) cases. Regarding evolution, healing without damage stands out for representing the majority of cases 249.372 (84.9%). It is noted the proportional growth of notification by toxic agent per year and the region of Brazil with the highest prevalence was the Southeast (51%) and the Federative Unit was São Paulo. Thus, the results indicate that there was an increase in the frequency of notifications, resulting from the irrational and indiscriminate use of medicines in the country.